2013
DOI: 10.1073/pnas.1307449110
|View full text |Cite
|
Sign up to set email alerts
|

Massively parallel in vivo enhancer assay reveals that highly local features determine thecis-regulatory function of ChIP-seq peaks

Abstract: Transcription factors (TFs) recognize short sequence motifs that are present in millions of copies in large eukaryotic genomes. TFsmust distinguish their target binding sites from a vast genomic excess of spurious motif occurrences; however, it is unclear whether functional sites are distinguished from nonfunctional motifs by local primary sequence features or by the larger genomic context in which motifs reside. We used a massively parallel enhancer assay in living mouse retinas to compare 1,300 sequences bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
263
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(297 citation statements)
references
References 40 publications
16
263
0
Order By: Relevance
“…We, and others before us, have shown that massively parallel enhancer-reporter assays can relatively quickly lead to such training sets, and usually lead to exciting new insight into the cis-regulatory logic of enhancers (Kwasnieski et al 2012;Melnikov et al 2012;Arnold et al 2013;Kheradpour et al 2013;White et al 2013). In our study, we tested long enhancer sequences, of several hundreds of base pairs.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 99%
See 3 more Smart Citations
“…We, and others before us, have shown that massively parallel enhancer-reporter assays can relatively quickly lead to such training sets, and usually lead to exciting new insight into the cis-regulatory logic of enhancers (Kwasnieski et al 2012;Melnikov et al 2012;Arnold et al 2013;Kheradpour et al 2013;White et al 2013). In our study, we tested long enhancer sequences, of several hundreds of base pairs.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 99%
“…A solution to this is to preselect the input, as has been done in the preset study, as well as recently in mice, using a STARR-seq-like approach, called CapStarr-seq (Vanhille et al 2015). The possibilities that these methodologies provide with regard to enhancer validation, both in vitro and in vivo (White et al 2013;Shen et al 2015), underscore the value and the need for such approaches in the field of regulatory genomics today.…”
Section: Tp53 Enhancer Logicmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, experimental advances have enabled characterization of the binding motifs for hundreds of TFs in vitro (5)(6)(7)(8)(9), mapping of the genome-wide binding sites of TFs in vivo (10)(11)(12)(13)(14), and functional characterization of the enhancer activity of thousands of genomic sequences (15)(16)(17)(18)(19). Comparisons between these experiments, however, have revealed that only a small fraction of the potential TF-binding sites (TFBSs) in eukaryotic genomes are actually occupied by TFs in any given cell type, and that these sites vary substantially across cell types and conditions (3,(19)(20)(21).…”
mentioning
confidence: 99%